Triple S Road - Alsaeed, Rajaa (2021)
This paper demonstrates a smart street-lighting system in travel highways. Travel highways in several regions around the world suffer from poor infrastructure conditions. These include potholes, damages, poor surfaces, and even lack of proper lighting. These conditions are the known causes of major accidents, especially during nighttime. In Kuwait, and according to Al-Jarida newspaper, Kabed Road, also known as the “death road,” has a high rate of car accidents due to such road conditions [1]. Besides losses in lives, car owners incur major expenses due to the car damages. Proposing solutions to make travel highways safer has positive impacts on society, the economy, and the environment. Continuous monitoring and proper lighting of highways appear to be effective approaches to guarantee safety over these highways. In this project we introduce Triple S Road; a system that aims at making travel highways safer by building a cost-effective monitoring system that overlooks highways to continuously check the traffic status, spot any emergencies or accidents, and control the road lighting. The system relies on both solar energy and wireless sensory to build a robust system that makes it safer to use travel roads overnight while reducing the costs of deployment and maintenance. In this project LED is used due to its low power consumption and environmentally friendly. The LED Street light is powered by a photovoltaic solar panel which is a renewable source of energy. The battery is added to store the overabundant energy of the photovoltaic solar panel that can be restored at nighttime and on cloudy days or other forms of shading. The LED light is controlled by sensor to switch on and off the light whenever vehicles or pedestrians pass by and off when no one around. Overall, Triple S Road is an intelligent system that utilizes cutting-edge technologies in sensors, energy resources, connectivity, and Web applications to provide a smart solution for a contemporary problem